Extension of banking hours. - Choo, Joo Kwang. (2013)
1975 saw the move by a local bank to extend Saturday banking hours. Since then, night-banking and Sunday banking were also introduced. This study was undertaken as we wanted to find out the necessity of such as a move in the age of electronic banking. A random sample of 319 was collected during the extended banking hours outside the branches which offer such a service. Our survey showed that 62.1% ofthe users visited the banks because they were busy during normal banking hours. The 3 services that were used most often wcre cash deposit, cheque deposit and passbook update.